Climacteric complaints among very low-income women from a tropical region of Brazil - Medeiros, Sebastião Freitas de; Medeiros, Márcia Marly Winck Yamamoto de; Oliveira, Vivaldo Naves de (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Climacteric symp- toms may vary between different countries and cultures. Socioeconomic factors and climate may be implicated. The aim of this study was to identify climacteric symptomatology among very low-income Brazilian women, living in a hot and humid region. DESIGN AND SETTING: This cross-sectional population-based study was conducted in Cuiabá, at Júlio Müller University Hospital, a tertiary institution. METHODS: The study enrolled 354 climacteric women. The variables analyzed were social class, symptomatology and abnormal concurent conditions. The study was approved by the hospital’s research ethics committee. RESULTS: Sixty-five percent of the participants (232/354) were very poor and had had little schooling. The number of symptoms per woman was 8.0 ± 5.7. Hot flushes, nervousness, forget- fulness and fatigue were each found in nearly 60.0%. Tearfulness, depression, melancholy and insomnia were also frequent. Sexual problems were reported by 25%. The most relevant concur- rent abnormal conditions reported were hyperten- sion (33.9%), obesity (26.5%), arthritis/arthrosis (15.0%) and diabetes mellitus (9.6%). Hot flushes were associated with tearfulness, nervousness and forgetfulness. CONCLUSION: Brazilian climacteric women of low income and low schooling present mul- tiple symptoms. Vasomotor and psychosexual symptoms were the most prevalent disorders. Hot flushes were associated with nervousness, forgetfulness and tearfulness.